Influence of Transactional and Transformational Leadership on Motivation A Study of Public Sector Universities in Karachi - Mangi, Abdul Rashid; Ashraf, Muhammad; Qadir, Abdul; Bhutto, Sarfaraz Ahmed (The journal of contemporary issues in business and government, 2021)
This study primarily focused on the analysis of transactional and transformational leadership influence on the Motivation level among the faculty associated with public sector universities. Motivation being the research construct has been a concern for the organizations as the studies witnessed (Page, 2008). Hence motivating the faculty has been regarded as the pivotal issue for the public sector universities because a motivated faculty perform well and influence the overall performance of the university and vice versa. Therefore the current study attempted to analyze the relationship between motivation and transformational, transactional leadership which may have a significant influence on motivation in public sector universities of Karachi.In addition, a comparison between male and female faculty members has been conducted to evaluate the effect of transformational and transactional leadership on their motivation levels.Meanwhile, the current study intended to explore the causal relationship between transactional, transformational leadership, and motivation, therefore the nature of this study was causal. Whereas, participants of the study were the faculty members of the public sector universities of Karachi. The findings of the study supported and accepted the hypotheses of the study as transactional and transformational leadership shares a significant and positive relationship with motivation among the faculty of public sector universities of Karachi.